Crystal structure of the co-crystal 2,4,6-triamino-1,3,5-triazine-1,3-dioxide — acetic acid (1/2) C7H14N6O6 - Wang Fei; Chen Cuilian; Suo Zhirong (Zeitschrift für Kristallographie - New Crystal Structures)
C7H14N6O6, monoclinic, C2/c (no. 15), a = 25.647(2) Å, b = 4.8865(4) Å, c = 21.585(2) Å, β = 111.500(6)°, V = 2516.8(4) Å3, Z = 8, R gt(F) = 0.0592, wR ref(F 2) = 0.1631, T = 100 K.